Diversity wild banana species (Musa spp.) in Sulawesi, Indonesia - HASTUTI HASTUTI; PURNOMO PURNOMO; I SUMARDI; BUDI S DARYONO (Society for Indonesian Biodiversity, 2019)
Abstract. Hastuti, Purnomo, Sumardi I, Daryono BS. 2019. Diversity wild banana species (Musa spp.) in Sulawesi, Indonesia. Biodiversitas 20: 824-832. Indonesia is known as one of the centers of banana diversity in the world. There are 70 species of wild banana in the genus of Musa, 12 of them it was found in Indonesia. Sulawesi was located in the Wallace Line, which is a meeting between the Sunda and Sahul exposures, and has many endemic species, some of which are wild banana species. However, studies on wild banana in Sulawesi are still limited. This study focuses on species of wild bananas found in Sulawesi. Purposive sampling was used to select banana example from wild, cultivated area, residential areas and research garden. Observation was carried out in the field as well as using a collection herbarium and living specimens. The observation was done by observing the characteristics of the sample according to the guidance on Descriptor for Banana. Identification was done by matching the sample with herbarium and relevant references. The results showed that there were four species of wild bananas found on the island of Sulawesi. These are Musa balbisiana Colla, Musa acuminata Colla var. zebrina (v.Houtte) Nasution, Musa acuminata Colla var. banksii (F.Muell.) N.W Simmonds, Musa acuminata Colla var. lutraensis, Musa acuminata Colla var. sigiensis, Musa acuminata Colla ssp. microcarpa Becc., Musa borneensis Becc. and Musa textilis Nee. Four wild banana accessions had never been reported before. These were Musa acuminata var. zebrina, Musa acuminata var. lutraensis, Musa acuminata var. siginenesis and Musa borneensis.